1965
DOI: 10.1130/spe84-p473
|View full text |Cite
|
Sign up to set email alerts
|

High Stands of Quaternary Sea Level Along the Chilean Coast

Abstract: Marine terraces partly cut in bedrock and partly filled or veneered with clastic deposits extend along much of the Chilean coast, particularly between the 23rd and 40th parallels. The highest terrace, about 250-400 m above present sea level in central and northern Chile, and 170-200 m above the sea in southern Chile, is probably Pliocene. Other terraces, at [30][31][32][33][34][35][36][37][38][39][40] and at 70 m,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][8][9][10] m in southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

1971
1971
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
7
0
3
Order By: Relevance
“…In fact, Fuenzalida et al (1965) had already noted that Chilean Coasts North of 40°S have been uplifting during the Pleistocene. These authors note that this Quaternary renewal of coastal uplift contrasts with the stability and/or subsidence that prevailed before the Middle Pleistocene (Fuenzalida et al, 1965 ;Paskoff, 1978 ;Clift & Hartley, 2007;Rodriguez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Fuenzalida et al (1965) had already noted that Chilean Coasts North of 40°S have been uplifting during the Pleistocene. These authors note that this Quaternary renewal of coastal uplift contrasts with the stability and/or subsidence that prevailed before the Middle Pleistocene (Fuenzalida et al, 1965 ;Paskoff, 1978 ;Clift & Hartley, 2007;Rodriguez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors, following Darwin (1846), noted that most of the Pacific coasts of South America are uplifting. Brüggen (1950) and Fuenzalida et al (1965) reported the presence of several marine terraces, partly cut in bedrock and partly filled or veneered with clastic materials along most of the Chilean coasts, particularly between 26°S and 40°S. They observed that the elevation of the highest terraces generally exceeds 150 m above mean sea level (m amsl).…”
Section: Introductionmentioning
confidence: 99%
“…Además, impulsó las primeras observaciones modernas sobre paleontología de vertebrados y su significado en la evolución del paisaje en el Cenozoico Tardío (Fuenzalida 1936 a y b). También se destacan sus estudios sobre terrazas marinas (Fuenzalida 1951a), coordinando además los resultados de investigaciones de distinguidos especialistas sobre este tema, dados a conocer en un simposio sobre el Cuaternario organizado por él (Fuenzalida et al 1965). Además, como una contribución novedosa al estudio de la evolución de paisajes en el Cuaternario, trabajó acerca de relaciones paleo geográficas entre suelos y vegetación (Fuenzalida 1951b) abriendo las puertas para trabajos futuros, no continuados por ausencia de especialistas.…”
Section: Prof Fuenzalida En Su Gabinete De Trabajounclassified